Аудит ризиків безпеки на робочому місці - Глива, Валентин Анатолійович; Березуцький, Вячеслав Володимирович; Березуцька, Наталія Львівна; Халіль, Вікторія Вячеславівна (Технологический центр, 2016)
Розглянуто теоретичні основи питання керування ризиками. На основі виконаного аналізу існуючих моделей менеджменту безпекою на виробництві та ризиками запропоновано модель ризику, яка складається з трьох визначених рівнів небезпеки, отриманих шляхом суб’єктивної, об'єктивної та зовнішньої оцінки ситуації на робочому місці. Загально інтегрована оцінка ризику свідчить про більш високу вірогідність рівня небезпеки.

The article describes the approaches to the problems of improvement of working conditions on the basis of existing risk calculation methods and a new integrated approach. Modern production is a complex in which an important place occupied by the person. Production increases its power and also increases the load on the person. Production capacity has various forms and types but the result is always the same - namely, the deterioration of the health of workers, the increase in the number of injuries and more. The entrepreneur must plan and optimize production capacity taking into account the resources of the human body. The article shows the levels of responsibility of officials and also shows that there are critical "nodes" that affect the general state of security in the enterprise and in some workplaces. OSH management system in the enterprise should be based on scientific principles and system analysis. On this basis, it is proposed to include the basics of system analysis is required to audit methods hazard risks in the workplace. This will allow more effectively and quickly identify risks and plan the work to reduce their level. A method for determining an integrated risk assessment in the workplace, taking into account the components of the audit process, can improve the reliability of the results and a more effective use. Qualified audit and analysis of the production loss is not possible without taking into account injuries and occupational diseases. The auditor should have objective information about all of the risks in the workplace, their proper accounting and distribution in company.
Audit of risks security of the workplace
Keywords: система; керування; стандарти; контроль; system; management; standards; control